English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

N = jane's current
M = Jim's current

N = 3*M
N+2 = 2(M+2) + 7 substitute the first in the second
3M+2 = 2M+11
M = 9
N = 3M = 27, Jane is 27

2007-02-20 02:50:11 · answer #1 · answered by TankAnswer 4 · 0 0

x = Jims age
3x = Jane's age
3x+2 =7 + 2(x+2)
3x + 2 = 7 + 2x + 4
x= 9
Jane's age = 3(9) = 27

2007-02-20 11:30:34 · answer #2 · answered by bignose68 4 · 0 0

*I am assuming that in 2 years Jane will be 7 years older than twice Jim's CURRENT age, not twice his age in 2 years. It matters what you assume.*
If we start to translate this into math, we have that
"Jane is 3x as old as Jim"
Jane = 3*Jim
We don't know how old Jim is so let's call his age x.
Jim = x so
Jane = 3*Jim = 3*x = 3x.
"In 2 years Jane..." = Jane +2 = 3x+2
"will be" means "="
so "In 2 years Jane will be ..." looks like 3x + 2 =
"7 years older than ..." means " add 7 to"
"twice as old as Jim." means 2*Jim = 2x.
OK, breathe... take it step by step and put it together.
Read the statement:
"In 2 years Jane will be 7 years older than twice as old as Jim."
3x + 2 = add 7 to 2x
3x + 2 = 2x + 7 now solve across the equal sign.
-2 -2
3x = 2x + 5
-2x -2x
x = 5, so Jim is 5 ***You haven't answered the question yet***
How old is Jane? 3*Jim = 3*5 = 15.

2007-02-20 11:05:18 · answer #3 · answered by watchlady 1 · 0 0

fedest.com, questions and answers